PRIMARY TIN CONCENTRATE FUMING PROCESS USING PIRITE AND GYPSUM MIXTURE IN A ROTARY KILN - Hibatullah, Zaidan
The second-largest tin reserves in the world is located in Indonesia. Tin reserves in Indonesia are alluvial and primary tin reserves but alluvial tin reserves are estimated to be exhausted within the next 5 to 10 years. To meet the demands for tin, PT Timah Tbk. started processing primary tin ore. Physical separation processing of primary tin ore is thought to be less effective at increasing the tin content in ore. Tin content is increased by more than 50% through the fuming process, which is used to raise the concentration of tin in the physical-processed concentrate. This research uses a mixture of pyrite and gypsum reagents to investigate the effects of temperature, the weight ratio of pyrite and gypsum, the mole ratio of S/Sn, the rate of tube rotation, and the flow rate of argon gas on the percent evaporation of tin as well as the amount of tin in dust. The research was carried out by mixing primary tin concentrates, coal, pyrite, and gypsum. The mixture was put into a cylindrical container and roasted at 950, 1050, and 1150°C. Roasting time is done for 3 hours. Argon gas is flowed into the furnace at a certain rate and the tube is rotated at a certain rate. The experimental results are in the form of residue in the cylinder container and dust at the end of the tube. The residue was analyzed using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), and Scanning Electron Microscope-Energy Dispersive Spectrometry (SEM-EDS) and the dust was analyzed using SEM-EDS to determine its chemical composition so that calculations may be conducted to determine the amount of tin evaporation and tin content in the dust. The effect of temperature was not visible in its tendency due to the excess sulfur addition in the experiment. However, a temperature of 950°C is sufficient to produce a tin evaporation rate of more than 90%. The use of a mixture of pyrite and gypsum with a higher percentage of pirite increases the tin evaporation percentage. The tin evaporation percentage and tin content in dust tend to increase with decreased tube rotation rate and argon flow rate. The experiment that obtained tin evaporation rates of more than 90% and tin content in dust greater than 50% had the following parameters: argon gas flow rate of 0.3 L/min; mol ratio S/Sn of 1.24; weight ratio of pyrite and gipsum 50% pyrite; coal amount of 8.25%; tube rotation rate of 1 rpm; temperature of 950°C; and roasting time of 3 hours. The amount of tin that evaporated was 96.4%, while the tin content in the dust was 56.95%.